Stephanofilariasis in Holstein Cows - Diagnostic Approach In Southern Brazil - Matos, Jane Karlla de Oliveira; Maldaner, Samoel Ricardo; Gruchouskei, Leonardo; Machado, Luciana; Zuliani, Fernanda; Cavalca, Alexandre Matheus Baesso; Alves, Carlos Eduardo Fonseca; Elias, Fabiana (Acta Scientiae Veterinariae, 2022)
Background: Stephanofilariasis is a parasitic disease caused by the nematode Stephanofilaria spp., considered a zoonotic disease, that affects several species, mainly dairy cattle. The condition causes chronic ulcerative dermatitis, due to the mechanical action of the parasite on the hair follicles and dermal papillae. The recommended diagnostic method is histopathological examination, but alternative methods have been studied for the detection of the agent since it does not demonstrate good results. There is no specific treatment, however, the use of organophosphates is recommended. The objective of this work is to report an outbreak of stephanofilariasis with unusual lesions in cattle from a dairy cattle farm in the city of Boa Vista do Buricá, RS, Brazil, as well as to demonstrate an alternative method for the diagnosis of the disease. Cases: We prospectively evaluated 15 Holstein cows, aged between 1 and 10-year-old whose data and materials for diagnosis, were provided by the property owner. The outbreak occurred in the summer, in a period of greater rainfall, affecting cows of different ages and totaling 48% of the herd. These showed ulcerative lesions on the skin of the groin, limbs and interdigital regions, and less frequently in the udder. The samples were obtained through tissue biopsy and scraped from the lesions, being packed in 10% formaldehyde for fixation. Afterward, the formaldehyde was centrifuged at 800 g for 5 min, which consisted of analyzing the sediment through optical microscopy and without staining, aiming at the direct search of the agent. The tissues, on the other hand, underwent routine processing and stained with Hematoxylin and Eosin. Histopathological analysis did not reveal Stephanofilaria sp. subjects in morphological analysis and revealed acanthosis, spongiosis, ulcers and fibrosis in the analyzed tissue. The examination of direct research with formaldehyde proved to be efficient, and fast. In the direct examination of the agent, structures similar to filarial and compatible with Stephanofilaria sp. in all samples. Thus, the present study demonstrated that filariasis can present in the form of outbreaks and with unusual injuries. The examination of direct research with formaldehyde, proved to be efficient and fast. Discussion: Semi-confined and confined animals may have a higher occurrence of strephanofilariasis, since the parasite needs humid and warm environments to proliferate and that, the proliferation of stephanophilariasis vectors is intensified in environments with low sunlight, high temperatures, high humidity, and low cleaning frequency. The city of Boa Vista do Buricá, where the outbreak occurred, reached a minimum average temperature of 18.5ºC and an average of 29ºC, with an average rainfall of 120.5 mm. Cutaneous lesions have been seen in animals from 1 to 10 years of age and no racial predisposition, age, or blackout stage is reported. The histological diagnosis, although mentioned as a form of diagnosis, has low efficacy in finding parasites in the tissue, is also used as a diagnosis, direct examination of the agent with saline solution, and impression of the lesion stained by the Romanoswsky method. However, in this report, formaldehyde proved to be a new option, as efficiently as saline. Keywords: filariasis, flies, nematode, dairy cattle, zoonotic disease, direct examination, lactation ulcer.